Prediction and Linguistic Awareness on Chronicle Reading on Virtual Tecnology and Non-Virtual Tecnology - Wannmacher Pereira, Vera (Lingüística y Literatura, 2017)
This article presents a reported study that examined the contribution of materials on virtual and non-virtual technologies with a focus on linguistic awareness in chronicles prediction reading to students in the 9th grade of high school. The Psycholinguistics was the theoretical support and Computer(s) the technical support. It involved materials production and the use of workshops development and use of pre-test and post-test. Results indicated a significant difference pre/post-tests in the awareness of the prediction use, and a favorable advantage of virtual technology, although with no statistically significant difference.